2022
DOI: 10.1039/d2ta06088d
|View full text |Cite
|
Sign up to set email alerts
|

CoFe alloy nanoparticles encapsulated in a 3D honeycomb-like N-doped graphitic carbon framework for photocatalytic CO2reduction

Abstract: The CoFe alloy nanoparticles (NPs) encapsulated in three-dimensional (3D) honeycomb-like porous N-doped graphitic carbon (CoFe/N-GC) frameworks were fabricated by a facile polymer thermal treatment method. Under UV-visible light irradiation, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…To evaluate the catalytic performance of Cu–C 3 N 4 -HA in CO 2 RR applications, a series of experiments were conducted in a flow cell reactor to evaluate its catalytic activity and selectivity. 55–60 LSV measurements were performed on C 3 N 4 , Cu–C 3 N 4 , and Cu–C 3 N 4 -HA to determine the optimal potential of the CO 2 RR. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the catalytic performance of Cu–C 3 N 4 -HA in CO 2 RR applications, a series of experiments were conducted in a flow cell reactor to evaluate its catalytic activity and selectivity. 55–60 LSV measurements were performed on C 3 N 4 , Cu–C 3 N 4 , and Cu–C 3 N 4 -HA to determine the optimal potential of the CO 2 RR. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16 Among them, owing to the superiority in regulating the electronic properties and strengthening the adsorption capacity of the CO 2 molecule or C 1 intermediates, modification of alloy nanoparticles (NPs) onto appropriate supports has been recently acknowledged to be an effective strategy for inducing high activity for targeted products in multiple electron-involved catalytic processes. 17–20 For instance, Xiong et al and Wang et al respectively supported alloy nanoparticles (Pd x Cu 1 or Pt x Cu 1− x ) on TiO 2 to synthesize alloy photocatalysts innovatively. 21,22 The results showed that the alloy co-catalysts improved CO 2 activation and promoted carrier separation, which led to excellent photocatalytic CO 2 -to-CH 4 conversion performance.…”
Section: Introductionmentioning
confidence: 99%
“…As more NO-C was added to the reaction system, the disordered assembly between some of the BMO nanosheets led to aggregation, which instead reduced the surface pore space and the specific surface area[33][34][35]. The inset in FigureS2shows that the BMO/NO-C catalysts exhibit a typical mesoporous structure, which provides not only abundant channels for the diffusion of CO 2 gas on the surface and inside the catalysts but also contributes many active sites for the adsorption and reduction of CO 2 , which is very beneficial for improving the photocatalytic CO 2 RR performance[36][37][38].The microstructure and morphology of the catalysts were characterized by using SEM. The inset of Figure2ahas shown that Bi 2 MoO 6 is spherical and composed of a large number of nanosheets.…”
mentioning
confidence: 99%